Study of Flow Rate Effect on Horizontal Flow Concrete Sand Filter Filtration Performance - Parsada, Laksmana Angga; Kamulyan, Budi; Triatmadja, Radianta (Journal of the Civil Engineering Forum, 2023)
The need for clean water during the pandemic is significantly increasing due to high public awareness of adopting a clean and healthy lifestyle (PHBS), necessitating more water treatment. Conventional methods are used for water treatment, including coagulation-flocculation system, rapid sand filter, and disinfection. However, these methods have limitations such as reduced capacity and sand filter efficiency, leading to increased backwash costs due to the need for sand replacement caused by particle stratification. In response to these challenges, an innovative method to water treatment is the use of concrete sand filter (CSF). Previous studies predominantly focused on downflow filtration, but there has been limited analysis of horizontal flow. Therefore, this study aimed to assess filtration and backwash effectiveness of CSF with horizontal flow, specifically focusing on the capacity performance in treating water with varying levels of turbidity. Filtration experiment was carried out using simulated water at turbidity of 125 NTU based on the Mataram Channel Turbidity with variations of 0.2, 0.5, 1.0, 5.0, and 10.0 m hour-1, as well as backwash at flow rate of 40.91 m hour-1 for 3 minutes. The variables measured during filtration process included head losses and turbidity at the inlet and outlet of CSF. The results showed that the capacity performance during filtration process was directly proportional to flow rate. Meanwhile, the effectiveness of concrete filter was inversely proportional to flow rate. At initial turbidity <617 NTU, the 3 minutes backwash process obtained lower final turbidity compared to the raw water used, which was 5.19 NTU. Meanwhile, at turbidity 617 NTU, the final turbidity was still high, reaching approximately 14.6–26.4 NTU.